Assessment of biofuels from waste cooking oils for diesel engines in terms of waste-to-energy perspectives. (March 2022) - Yildiz, Ibrahim; Caliskan, Hakan; Mori, Kazutoshi
Highlights: Generation of sustainable and renewable biofuel from waste cooking oil. Determination of new fuel properties of acid number, density, kinematic viscosity, cloud point, flash point and pour point for new renewable fuels. Investigating the diesel and new biodiesel fuels in terms of waste-to-energy perspective. Comparisons of the emissions and nanoparticles of fuels. Abstract: In this study, specific biofuel is produced from waste cooking oils and investigated on the basis of "waste-to-fuel/energy" perspective. Then, the fuel properties (viscosity, density, cloud point, flash point, acid number, lower heating values and pour point) of produced biofuel and diesel are obtained. The exhaust emissions resulting from the combustion of the fuels used in the internal combustion diesel engine at 100 Nm load are experimentally investigated. The kinematic viscosity of produced biofuel is found as 6.270 mm 2 /s. However, the kinematic viscosity of diesel fuel is determined as 3.743 mm 2 /s. The use of biofuel is expected to cause more fuel consumption than the use of diesel fuel. The emissions are also affected by this situation. The density of produced biofuel is obtained to be 882 kg/m 3, while the density of diesel fuel is found as 831 kg/m 3 . High fuel density affects emissions and engine performance negatively, and biofuel has a higher density value than diesel fuel. It can be concluded that the waste oil derived biofuel affects are different than diesel fuel affects considering same diesel engine for the comparison. So, it is important to generate new types of biofuels to reach the optimum results for the engine and environment.